Literature Review: Ibnu Khaldun Philosophy of Islamic Education an Integrative Framework for Contemporary Pedagogy - Erdiyanti; Dirman (IAIN KENDARI, 2025)
Ibn Khaldun’s philosophy of Islamic education presents a comprehensive and integrative perspective that remains deeply relevant to modern pedagogical discourse. This study aims to explore and synthesize Ibn Khaldun’s core educational concepts tarbiyah (development), ta‘līm (instruction), and ta’dīb (ethical cultivation) as a potential framework for addressing contemporary challenges in Islamic education. Using a qualitative approach through a systematic literature review (SLR), the study analyzed nine scholarly articles published between 2021 and 2025. The findings reveal that Ibn Khaldun emphasized the holistic development of learners, not only intellectually but also morally and spiritually, with the goal of producing the insān kāmil (complete human being). His vision of education integrates rational knowledge with divine revelation and aligns with current educational needs such as ethical grounding, learner-centered models, and value-based curriculum design. The discussion highlights that applying Ibn Khaldun’s philosophy to today’s educational systems can offer innovative, ethically rooted, and context-sensitive solutions. This review concludes that his educational framework is highly applicable to shaping future-oriented, morally responsible Islamic pedagogy.